PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Rachman, Heddy Arif; Nopiyanti, Anita (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2015)
The purpose of this study was to examine the influence of probability, leverage, and company size to corporate social responsibility disclousure. The independent variables in this study is probability, leverage, and company size. The dependent variable in this study is the corporate social responsibility disclousure, with years of research for 2010-2013. The sample in this study is mining companies that go public in Indonesia Stock Exchange (BEI) and have reported the corporate social responsibility disclosure activities. There are 36 samples by purposive sampling method. This study uses multiple linear regression analysis. The results showed that there was no significant relationship between profitability and leverage on the disclosure of corporate social responsibility. Instead, there is a significant influence in the presence of company size on disclosure of corporate socialresponsibility.